Sosialisasi Bank Sampah untuk Meningkatkan Kepatuhan Pengelolaan Sampah di Desa Pemecutan Kaja - I Putu Ditya Ariesannya Baskara; Anak Agung Adi Wiryya Putra; Putu Radika Rani; Ni Kadek Feby Rahmawati; I Putu Arya Suartama (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Waste management remains one of the environmental issues in urban areas, including Denpasar City. The low level of public awareness in sorting waste from the source and the limited community participation in waste bank management have become challenges in realizing sustainable waste management. This community service activity aims to increase public understanding of waste management and the role of waste banks as part of a community-based waste management system. The activity was conducted through a socialization program involving 45 participants who were core members of the PKK women’s group representing each banjar in Pemecutan Kaja Village, Denpasar City. The materials presented included household waste management, regulations related to waste management and the rights and obligations of the community in maintaining environmental sustainability, as well as the introduction of recording and bookkeeping systems in waste bank management. The results of the activity indicate that the socialization increased participants’ understanding of the importance of sorting waste at the household level and managing waste banks more systematically. In addition, the introduction of a waste bank recording system also attracted participants’ attention as an effort to support more organized waste bank management at the community level.